A probabilistic model for predicting reliability performance of distribution substation using minimal cut set method - Gonzales, Allen C. (2005)
This study developed a method to predict the reliability performance of distribution substations using minimal cut set method in building reliability network models and basic reliability parameters such as failure rates and repair rates of substation components. Reliability models for four typical designs of distribution substations were developed. The effectiveness and accurateness of the proposed approach was validated on existing distribution substations of Manila Electric Company (MERALCO) where predicted performances of the substations are compared with their historical performances. The proposed methodology was also applied to a future substation development project of MERALCO with a single breaker-single bus scheme having one transformer bank. Predicted reliability performance of this project was compared with the ring bus and breaker-and-a-half substation configurations as alternate schemes. The models developed in this study have made possible the quantitative reliability comparisons between alternative design schemes of future distribution substation projects that are useful in conducting cost-reliability tradeoff studies.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric substations -- Philippines; Electric power distribution -- Philippines; Electric power systems -- Philippines; Electric utilities -- Philippines